K voprosu o sovremennykh tendentsiyakh razvitiya sporta - Zotova, F. R.; Chinkin, A. S. (Teorija i Praktika fiziceskoj Kul'tury, 2001)
Recently a plenty of researches has appeared, in which the state of modern sports is estimated. Their analysis allows to reveal the following basic tendencies in the development of sports observed in the last decade: 1. The significant growth of sports achievement 2. The significant rise in price of sports competitions 3. The fast rejuvenation of sports 4. The professionalization of sports 5. The crisis of Olympism. 6. The occurrence of new kinds of sports The authors have made an attempt to show the basic tendencies in the development of modern sports, which is characterized by both positive and negative directions demanding the further analysis, judgement and decision.